Teaching Students With Intellectual Disability to Integrate Reading Skills: Effects of Text and Text-Based Lessons. (November 2013) - Allor, Jill H.; Gifford, Diane B.; Al Otaiba, Stephanie; Miller, Saralyn J.; Cheatham, Jennifer P.
This multiple baseline study investigated the effectiveness of text-based reading lessons for students with intellectual disability (ID). Three students were selected who had not responded well to explicit and systematic reading instruction. They were provided with individual instruction in daily 45-min sessions for 14 weeks (approximately 70 sessions). All three students increased the number of words read from baseline (ranging from 5 to 20 words correct) to the final intervention session (ranging from 40 to 75 words correct), though one student's data were less conclusive due to growth during the baseline phase. Regression discontinuity revealed the intervention caused statistically significant growth. The intervention is promising given that students with ID who initially did not respond to systematic instruction improved their ability to sound out and unitize (i.e., read with automaticity) words.